Public-Private Partnerships in the Caribbean Region : Reaping the Benefits while Managing Fiscal Risks - Queyranne, Maximilien (Departmental Papers; Departmental Paper ;, 2019)
To provide policymakers in the Caribbean with a governance framework for improving infrastructure through Public-Private Partnerships (PPPs), while limiting their fiscal costs and risks for the government. And to showcase Canada support to FAD technical assistance in the region and FAD collaboration with CARTAC and the Caribbean Development Bank.